Hydraulic conductivity and geophysics (ERT) to assess the aquifer recharge capacity of an inland wetland in the Brazilian Savanna - César Augusto Moreira (Environmental Challenges, 2021)
The inland wetlands can perform the storage of water on the surface and the recharge of aquifers. Even a small wetland can work as a local point of water infiltration, influencing and sustaining the hydrodynamics in the hydrology landscape. These zones have complex mechanisms, as they integrate soil chemical and physical characteristics, and relate both surface and groundwater systems. The study area is an inland wetland located in the Ecological Station of Itirapina, São Paulo State (Brazil). The present work aims to unveil the relationship between hydrodynamics and pedological architecture through a detailed study that combines hydraulic conductivity tests in situ, geophysical method of electrical resistivity (Electrical Resistivity Tomography technique, ERT), and morphological soil descriptions aiming the validation of the ERT and hydraulic conductivity surveys. Two-dimensional (2D) and pseudo-three-dimensional (3D) ERT have been used to investigate the water flow in the subsurface, the pedological architecture that keeps the wetland hydroperiods, and the link between surface water and groundwater that can set a recharge capacity. The results showed areas with distinct surface patterns related to the density of vegetation cover and water infiltration. The lower infiltration areas are characterized by the presence of a perched water table in grassy areas while higher infiltration is associated with exposed topsoil. ERT 2D and pseudo-3D identified these areas as zones with a connection between soil-water and groundwater systems. Hydrodynamics in the flat plateau is associated with the geochemical evolution of soil cover due to the structural complexity acquired by the iron crust dissolution (laterite) which has sustained the relief. Future studies concerning inland wetlands need to be carried out to certify the role of soil-landscape in the water cycle in the Savanna biome.